DIGITALISASI DAN REPOSITORI DOKUMEN PADA DESA KARANGDUREN KEC.PAKISAJI, KAB.MALANG UNTUK MENINGKATKAN PELAYANAN MASYARAKAT - Yuri Arianto; Atiqah Nurul Asri; Mungki Astiningrum; Yoppy Yunhasnawa; Toga Aldila Cinderatama; Yan Watequlis Syaifudin (P3M Politeknik Negeri Malang, 2023)
Village administration's core lies in directly addressing community needs. However, Karangduren village in Kab. Malang faces challenges due to its reliance on traditional paper-based governance. This leads to recurring difficulties in managing documents. To tackle these issues, the proposed Community Service (PPM) initiative,